The association between patient activation and healthcare resources utilization: a systematic review and meta-analysis. (September 2022) - Anderson, G.; Rega, M.L.; Casasanta, D.; Graffigna, G.; Damiani, G.; Barello, S.
Abstract: Objectives: To measure the association between patient activation and hospitalization or emergency department (ED) visits among adults with chronic diseases. Study design: Systematic review and meta-analysis. Methods: A systematic review of English articles was performed using the following databases: PubMed, Cochrane Library, Web of Science, PsycINFO, and Embase. Articles were searched from 2005 until July 2021. Observational studies that measured the association between patient activation, measured by the Patient Activation Measure (PAM), and hospitalization or ED visits among adults with chronic or multichronic diseases were included. Pairs of reviewers independently screened the studies and extracted data for qualitative and quantitative synthesis. The methodological quality was assessed using the Quality in Prognostic Studies (QUIPS) tool. Results: A total of nine observational studies (153, 121 participants) were included in the qualitative synthesis, whereas six were pooled in the quantitative synthesis (151, 359 participants). High levels of patient activation were significantly associated with a reduced risk for both hospitalizations (RR [95% CI] = 0.69 [0.61; 0.77], I 2 = 78%) and ED visits (RR [95% CI] = 0.76 [0.70; 0.84], I 2 = 72%). Conclusions: Our findings suggest the existence of an inverse association between patient activation and healthcare resources utilization. Further observational studies are needed to fully comprehend the magnitude of this association.